2022
DOI: 10.3389/fped.2022.881765
|View full text |Cite
|
Sign up to set email alerts
|

Multisystem Inflammatory Syndrome Temporally Related to COVID-19 in Children From Latin America and the Caribbean Region: A Systematic Review With a Meta-Analysis of Data From Regional Surveillance Systems

Abstract: BackgroundWith the emergence of the COVID-19 pandemic, increasing numbers of cases of the multisystem inflammatory syndrome in children (MIS-C) have been reported worldwide; however, it is unclear whether this syndrome has a differential pattern in children from Latin America and the Caribbean (LAC). We conducted a systematic review and meta-analysis to analyze the epidemiological, clinical, and outcome characteristics of patients with MIS-C in LAC countries.MethodsA systematic literature search was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 56 publications
4
12
0
4
Order By: Relevance
“…They were “wuhan strains” (February 2020 - February 2021), “alpha” (February 2021 - July 2021), “delta” (July 2021 – December 2021). The first cases of MIS-C in children began to be registered approximately 2,7 months after the outbreak of the epidemic in the country and a month after the detection of severe COVID-19 in children, which is quite consistent with the data of other studies [16, 37, 38]. The largest number of patients – 40 (66,7%), were admitted to inpatient treatment during the circulation of the “wuhan strains” of SARS-CoV-2.…”
Section: Discussionsupporting
confidence: 91%
“…They were “wuhan strains” (February 2020 - February 2021), “alpha” (February 2021 - July 2021), “delta” (July 2021 – December 2021). The first cases of MIS-C in children began to be registered approximately 2,7 months after the outbreak of the epidemic in the country and a month after the detection of severe COVID-19 in children, which is quite consistent with the data of other studies [16, 37, 38]. The largest number of patients – 40 (66,7%), were admitted to inpatient treatment during the circulation of the “wuhan strains” of SARS-CoV-2.…”
Section: Discussionsupporting
confidence: 91%
“…In a cohort of 557 severe and critical COVID-19 pediatric patients from North America, Latin America, and Europe, the overall hospital mortality was 10%, but 15% in children <2 years (OR 1.89; 95% CI, 1.05-3.39); 50% of the patients had comorbidity and 83% received antibiotics. Those with MIS-C had a lower mortality risk (OR 0.26; 95% CI, 0.11-0.64) (26) in contrast with other reviews from Latin America that found an overall case fatality ratio of 4% in 592 MIS-C cases (30). In a systematic review and meta-analysis that included 83 studies, 57 (21,549 patients) in the meta-analysis (of which 22 provided individual patient data) and 26 studies in the narrative synthesis, the authors found that hospitalized children and young people at the greatest vulnerability to severe disease or death with SARS-CoV-2 infection are infants, teenagers, those with cardiac or neurological conditions, or 2 or more comorbid conditions, and those who are significantly obese (31).…”
Section: Discussionmentioning
confidence: 99%
“…It is relevant and essential to examine the clinical characteristics, disease management, and outcomes of MIS-C due to the potentially severe consequences such as death (16)(17)(18), damage to coronary arteries, and the toll on healthcare resources necessary for its management. The present cohort's mortality rate was 4.6%, which exhibited high heterogeneity across the centers, ranging from 0% to 13.5%.…”
Section: Discussionmentioning
confidence: 99%